Sustaining extraordinary student achievement - Reksten, L.E. Linda E. Reksten (Thousand Oaks: Corwin Press, 2009)
The patterns described in these successful schools both validated and challenged my thinking. I can see opportunities for renewed emphasis in our district and much hope for continuing our progress with students.
Includes bibliographical references and index.
Keywords: School improvement programs -- California -- Case studies; Academic achievement -- California -- Case studies